Isolation and Identification of Bacteriocin-Producing Lactic Acid Bacteria from Urutan, Balinese Traditional Fermented sausage - Dwijastuti, Ni Made Sri; Sujaya, I Nengah; Fatmawati, Ni Nengah Dwi (Metamorfosa: Journal of Biological Sciences, 2021)
This study aimed to isolate and identify lactic acid bacteria (LAB) that could produce bacteriocins from urutan. Urutan is a Balinese sausage that is traditionally produced and naturally fermented. Urutans used in this study were obtained from several traders in the Baturiti, Mengwi, and Tegallalang region, Bali. More than 300 LAB colonies were isolated and underwent inhibition test against the growth of the indicator bacteria. Crude bacteriocins from two isolates, namely J2 and J6, showed inhibition zones against the growth of Lactobacillus plantarum E12.1 and Escherichia coli ATCC 8739. The J6 isolate also inhibited the growth of Enterococcus faecalis ATCC 29212. Both J2 and J6 were gram-positive, bacilli shaped, and showed negative catalase test. Based on the results of the 16S rDNA gene amplification, the two isolates were identified as Lactobacillus plantarum . Keywords : Lactic Acid Bacteria, Bacteriocin, Lactobacillus plantarum , Urutan